Pengaruh Model Student Achievement Achievement Division Terhadap Hasil IPS Kelas IV Sekolah Dasar - Yulianti, Yulianti; Nasrul, Nasrul; Mayarnimar, Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research was undertaken as an attempt to assess the effect of cooperative learning model: Student Teams Achievement Divisions (STAD) on the fourth grade students’ learning outcomes in Social Science at SD Negeri 10 Bandar Buat. This research adopted a quasi-experimental research design with the non equivalent control group design. The population of this study was all of the fourth grade students at SDN 10 Bandar Buat that were divided into experimental group (class IVA) and control group (class IVB). Based on the calculation of t-test, t-count (2.18) scored higher than t-table (2.01) at significance level 0.05. The mean score of the experimental group was 80.25 and the mean score of control group was 76.04.   Therefore, in this case, the hypothesis H1 was accepted.